Sustainable agriculture - Mason, John, 1951- (Collingwood, Vic. : Landlinks Press, 2003)
This book is about foreseeing and understanding the problems associated with the technological revolution in farming practices, and explains the concepts and long-term benefits of sustainable farming systems.
1. Different things to different people -- 2. Sustainable concepts -- 3. Soils -- 4. Water management -- 5. Pest and disease control -- 6. Sustainable natural weed control and cultivation -- 7. Management -- 8. Managing plants: crops and pastures -- 9. Managing plants: tree plantings and windbreaks -- 10. Managing animals in a more sustainable way -- 11. Understandable products used in sustainable agriculture.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Sustainable agriculture; Sustainable development; Agriculture durable; Développement durable; sustainable development; sustainable agriculture (discipline); TECHNOLOGY & ENGINEERING -- Agriculture -- Agronomy -- Crop Science; TECHNOLOGY & ENGINEERING -- Agriculture -- Agronomy -- General; Sustainable agriculture; Sustainable development; Sustainable agriculture; Sustainable development; Nachhaltigkeit; Biologische Landwirtschaft; Landwirtschaft; Agricultura sustentável.; Permaculture; Agriculture durable